2012
DOI: 10.1097/mao.0b013e31826dba5f
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Early Loading of Osseointegrated Implants for Bone Conduction at 4 Weeks

Abstract: Successful early loading of the BAHA sound processor has been achieved. RFA provides a reliable means of assessing stability for loading and measuring implant stability in the longer term. These data support the evidence for early loading at 4 weeks with good clinical safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 12 publications
5
32
0
Order By: Relevance
“…The six-month report showed higher mean Implant Stability Quotient (ISQ) values and less soft tissue reactions for the new, wider implant compared to the previous generation implant. The good outcomes could be confirmed in other studies [3][4][5] and in long term follow up [6], and resulted in a complete substitution of the previous generation implant in all new BAHI surgeries, not only in adult patients but also in the pediatric population. During the last few years, however, in both centers, we noticed a high incidence of soft tissue reactions, revision surgery and non-users in our pediatric BAHI population.…”
Section: Introductionsupporting
confidence: 52%
“…The six-month report showed higher mean Implant Stability Quotient (ISQ) values and less soft tissue reactions for the new, wider implant compared to the previous generation implant. The good outcomes could be confirmed in other studies [3][4][5] and in long term follow up [6], and resulted in a complete substitution of the previous generation implant in all new BAHI surgeries, not only in adult patients but also in the pediatric population. During the last few years, however, in both centers, we noticed a high incidence of soft tissue reactions, revision surgery and non-users in our pediatric BAHI population.…”
Section: Introductionsupporting
confidence: 52%
“…14 Use of the same implant processor with loading at four weeks has also been shown to be viable. 9 In a study of a linear incision surgical technique with no skin thinning, using both Cochlear and Oticon Medical implant systems, healing time was reported to be significantly shorter for the test group than for a control group who underwent surgery with a dermatome procedure. The skin of all patients in the test group healed within 10 days.…”
Section: Discussionmentioning
confidence: 98%
“…There appears to be little difference in the risk of osseointegration failure for those patients loaded at less than 6 weeks or more than 12 weeks, or even at 4 weeks post-operatively. [8][9][10] Recent advances in fixture technology include a wider diameter fixture to increase the bone-fixture contact area and novel fixture coatings to speed up osseointegration. 11 Both of these may permit earlier loading than has traditionally been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Faber et al [25] and McLarnon et al [26] confirmed implant stability with early loading at 3 weeks and 4 weeks respectively. Additionally, an unpublished report presented at the Third International Symposium on Bone conduction Hearing and Craniofacial Osseointegration (Sarasota, FL) by Green et al confirmed implant stability with early loading at 2 weeks.…”
Section: Grade Clinical Descriptionmentioning
confidence: 62%